Reference values for six-minute walk test in apparently healthy Nigerian adults (African Journal of Biomedical Research, 2022)
The six-minute walk test (6MWT) is a common utility outcome for evaluating exercise capacity in patients with pulmonary diseases. However, there is no existent reference value for Nigerian older adults. This study is therefore aimed at establishing reference values and equations for 45-70 years old Nigerian adults. We consecutively recruited apparently healthy adults into this cross-sectional survey and used standard protocols for 6MWT and anthropometrics. Regression equations were developed based on demographic and anthropomorphic data. These equations were compared to existing prediction equations. One hundred and four participants completed two 6MWT. The average six-minute walk distance (6MWD) was 378 metres; greater in men than women (p